The principles of Native administration in the Anglo-Egyptian Sudan 1898-1956. By Ahmad Ibrahim AbouShouk and Anders Bjorkelo. Sudan: Abdel Karim Mirghani Cultural Center (Omdurman) and Center for Middle Eastern and Islamic Studies (Bergen) 2004, pp. 279. - Eisa, Garout Suliman (IIUM Press, 2005)
This book is essentially a collection of documents pertaining to the evolution of the institutions of Native Administration introduced by the Colonial Administration of the Sudan. This institution was gradually reformed throughout what was known as the Condominium Rule in the Sudan established in the wake of the joint occupation of the country by British and Egyptian armies after they defeated the Mahdist forces in 1898.